Anesthesia Residency Training in Airway Management: A Competency-Based Model Curriculum. Issue 5 (1st September 2019) - Galway, Ursula A.; Straker, Tracey; Foley, Lorraine J.; Aziz, Michael; Woodworth, Glenn
Abstract : The Accreditation Council for Graduate Medical Education (ACGME) is moving toward competency-based medical education. This educational framework requires the description of educational outcomes based on the knowledge, skills, and behaviors expected of competent trainees. An assessment program is essential to provide formative feedback to trainees as they progress to competency in each outcome. This article describes the development of 2 model curricula for airway management training (basic and advanced) using a competency-based framework. Abstract : Supplemental Digital Content is available in the text.